Answer:
Solution: (3, -1)
Explanation:
Given equations:
Step-1: Reorganize the equations with "y" on the L.H.S
![\rightarrow \left \{ {{4x + 5y = 7} \atop {y = 3x - 10}} \right.](https://img.qammunity.org/2023/formulas/mathematics/high-school/i1b2f4q4na01s5abtcashjmkqjykumnw44.png)
![\rightarrow \left \{ {{5y = 7 - 4x} \atop {y = 3x - 10}} \right.](https://img.qammunity.org/2023/formulas/mathematics/high-school/eoy9oai5jfbolwpwhlt17dghjtihkuwoyv.png)
![\rightarrow \left \{ {{5y = 7 - 4x} \atop y =-10 + 3x}} \right.](https://img.qammunity.org/2023/formulas/mathematics/high-school/qdgus95l18tvqe8n638xmsndglntznxzxu.png)
Step-2: Make the x-variables the same on both equations
![\rightarrow \left \{ {{3(5y = 7 - 4x)} \atop 4(y =-10 + 3x)}} \right.](https://img.qammunity.org/2023/formulas/mathematics/high-school/z7n63wks1g4foxl3rm0hf23wuo5qa14i42.png)
![\rightarrow \left \{ {{15y = 21 - 12x} \atop 4y =-40 + 12x}} \right.](https://img.qammunity.org/2023/formulas/mathematics/high-school/fs82mpmpnea3sxt6nsrsrem9sj0qctequc.png)
Step-3: Add the equations
![\rightarrow (15y + 4y) = (21 - 40) + (-12x + 12x)](https://img.qammunity.org/2023/formulas/mathematics/high-school/uwu8ip4ihes5atdd2wz6pbde6lcthxuc4h.png)
![\rightarrow 19y = -19](https://img.qammunity.org/2023/formulas/mathematics/high-school/yovguux1bqxa76gp8cbnvkdr76uuknm4ok.png)
Step-4: Divide both sides by 19
![\rightarrow (19y)/(19) = (-19)/(19)](https://img.qammunity.org/2023/formulas/mathematics/high-school/dx40dmggco8fpww8yx73k3kys2igq9qdy3.png)
![\rightarrow y = -1](https://img.qammunity.org/2023/formulas/mathematics/high-school/tgsoxh5mss70j2nrtsh5o3jmd0divr4os1.png)
Step-5: Substitute the value of y into any equation
![\rightarrow y = 3x - 10](https://img.qammunity.org/2023/formulas/mathematics/high-school/6evnp5i7xum0os9ey58ta58x6uucing9rm.png)
![\rightarrow -1 = 3x - 10](https://img.qammunity.org/2023/formulas/mathematics/high-school/2cdq0tlupctkig14c4zg8mcafxfq4dvwni.png)
Step-6: Simplify the equation
![\rightarrow -1 + 10 = 3x](https://img.qammunity.org/2023/formulas/mathematics/high-school/ed8ciqat7kkbuougl5yvs6fcdoqe1jdquf.png)
![\rightarrow9= 3x](https://img.qammunity.org/2023/formulas/mathematics/high-school/pnn5xb0926p0yywz8g1xnid578rhj4pthy.png)
Step-7: Divide 3 both sides
![\rightarrow (9)/(3) = (3x)/(3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/ku8j12dz3wdald1j8awfqqzgxevcwthviy.png)
![\rightarrow x = 3](https://img.qammunity.org/2023/formulas/mathematics/high-school/obparnidgn03qn652685hmdqnp77uacpzf.png)
(Optional) Step-8: Convert the solution(s) into (x, y) form
![\rightarrow (x, y) \rightarrow (x = 3; y=-1) \rightarrow (3,-1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/1c6uq7xwdcxlaixuxtq35ho4964flipw3f.png)
Thus, the value of x and y is 3 and -1. The solution is (3, -1).